The Effectiveness of Problem Based Learning Model With The Assistance of Animation Media on Tetragon Material To The Students Mathematic Learning Achievement of Grade Vii Smp Negeri 5 Mandai - Nasir, A. Muhajir; Hadijah, Hadijah (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
This research was an experimental research that aimmed to know and measure the effectiveness of the application of Problem Based Learning model (PBL) with the assistance of animation media on tetragon material. This research type was quantitative research with one group pretest-posttest design. The population in this study was the students of class VII SMP Negeri 5 Mandai with a random sample of 28 students in an experimental class. Data collection using a test of learning achievement that has been validated by the expert. The data of this research were analyzed descriptively and inferential with normality test as prerequisite analysis test. The results of the data analysis showed that the average pre-test was 45,57 while the average post-test was 84,32. Average gain scores normalized 0,72 in the high category and normally distributed for learning achievement data. Based on the t-test obtained 0,000 < Î± = 0,025 we could conclud that there was a significant increase. The post-test also showed that 26 out of 28 students (92,86%) have reached KKM score in mathematics in SMP Negeri 5 Mandai. The results of this study indicate that there was a significant improvement on the mathematics learning achievement of students after being taught with PBL model with the assistance of animation media on tetragon material.